HUBUNGAN PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS DEWANTARA KABUPATEN ACEH UTARA - Maulina Maulina; Jasmiati Jasmiati; Nurlaili Ramli (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2026)
The importance of complementary feeding to prevent stunting is because complementary feeding is an important step in a child's development after six months of age. Choosing the right type of food during this period can have a major impact on a child's growth and development. Data from Aceh Province in 2022 shows that 321,709 toddlers were weighed and measured, with 29,819 toddlers (9.3%) suffering from stunting. The highest number of stunted toddlers was found in Aceh Besar District, with 4,974 cases (17.5%). In North Aceh District, 35,992 toddlers were weighed and measured, with 2,735 toddlers (7.5%) suffering from stunting. This study is a quantitative study using a cross-sectional study. The frequency distribution results for complementary feeding showed that the majority were in the inappropriate category, with 38 people (62.3%), while the majority of stunting cases were in the non-stunting category, with 41 people (67.2%). The chi-square test yielded a p-value of 0.002 < (α) = 0.05, indicating a significant association between complementary feeding and stunting among infants at the Dewantara Health Center in North Aceh District in 2025. There is an association between complementary feeding and stunting among infants